Implementation of STEAM-Based Islamic Education Learning Through the Utilization of the Wayground Platform - Naufal Hafidh; Diah Wahyuningsih (Hikmah, 2026)
Islamic Religious Education learning in the contemporary era faces major challenges in responding to globalization, where religion is expected to provide solutions to various social and educational problems. To address these challenges, learning activities were implemented through a STEAM-based approach supported by the Wayground digital platform. This study employed a qualitative method conducted at Madrasah Diniyah Fathul Ulum, Pacitan, East Java. The study aimed to describe the implementation of STEAM-based learning through the utilization of the Wayground platform in Islamic Religious Education instruction. Data were collected through observation, interviews, and documentation. The findings showed that STEAM-based Islamic Religious Education learning could be effectively implemented in fiqh learning on the topic of understanding the qibla direction through practical activities involving the creation of a simple compass. STEAM elements were integrated through scientific explanations of Earth’s magnetic field, engineering activities in constructing the compass, artistic activities in drawing compass diagrams, and mathematical calculations for determining the qibla angle. The Wayground platform supported learning through interactive features such as video quizzes, presentations, and mix-and-match activities, which created a more communicative, contextual, and engaging learning environment.